P434 Substance use patterns and HIV prevention among gay and bisexual men in the 2014–2015 sex now survey. (14th July 2019) - Card, Kiffer; Higgins, Robert; Tooley, Len; Ablona, Aidan; Trussler, Terry; Jollimore, Jody; Lachowsky, Nathan
Abstract : Background: Qualitative studies suggest that substance use is central to the identities and cultures of many gay and bisexual men (gbMSM) – and a salient factor in how they manage HIV risk. To quantitatively assess this, we examined patterns of substance use and associations with awareness, interest, and uptake of key prevention strategies. Methods: Canadian gbMSM were recruited online and asked to report their frequency of substance use. Latent class analysis identified patterns in use. Demographic-adjusted multivariable multinomial logistic regression models, stratified by HIV-status, assessed associations with key prevention strategies (TasP awareness, PrEP interest, HIV-testing). Results: Among 669 HIV-positive and 7, 184 HIV-negative men, six substance use classes were characterized: 'limited' (46.0%; i.e., infrequent/low use of most drugs), 'conventional' (25.9%; i.e., alcohol, marijuana, and tobacco), 'club' (9.5%; i.e., alcohol, cocaine, and psychedelics), 'sex' (11.4%; i.e., alcohol, crystal meth, GHB, poppers, and erectile dysfunction drugs), 'prescription' (12.1%; i.e., alcohol and prescription drugs), and 'assorted' (4.5%; i.e., most drugs) use. Limited use was selected as the referent class in all analyses. Other HIV-positive men were no more likely to have detectable viral-loads, nor were they less likely to know about the preventative benefits of TasP. HIV-negative men in the prescription (aOR:1.37, 95%CI:1.15–1.63) and sex (aOR:1.58, 95%CI:1.21–2.06) drug use classes were more likely to know about TasP. HIV-negative men in the prescription (aOR:1.6, 95%CI:1.34–1.91), conventional (aOR:1.30, 95%CI:1.16–1.45), club (aOR:1.44, 95%CI:1.15–1.81), sex (aOR:3.94, 95%CI:2.92–5.33), and assorted (aOR:3.06, 95%CI:1.64–5.72) use classes were more likely to report interest in taking PrEP. Membership in these classes was associated with higher odds of HIV-testing. Conclusion: Among HIV-positive men, we observed high levels of viral-load undetectability and TasP awareness, independent of substance use. Among HIV-negative men, multiple patterns of substance use traditionally associated with heightened risk for acquiring HIV were associated with awareness, interest, and uptake of HIV risk management strategies, contravening stereotypes that link substance use to risk-indifferent attitudes. Disclosure: No significant relationships.